Slow-Theta-to-Gamma Phase–Amplitude Coupling in Human Hippocampus Supports the Formation of New Episodic Memories. (14th October 2014) - Lega, Bradley; Burke, John; Jacobs, Joshua; Kahana, Michael J.
Abstract: Phase–amplitude coupling (PAC) has been proposed as a neural mechanism for coordinating information processing across brain regions. Here we sought to characterize PAC in the human hippocampus, and in temporal and frontal cortices, during the formation of new episodic memories. Intracranial recordings taken as 56 neurosurgical patients studied and recalled lists of words revealed significant hippocampal PAC, with slow-theta activity (2.5–5 Hz) modulating gamma band activity (34–130 Hz). Furthermore, a significant number of hippocampal electrodes exhibited greater PAC during successful than unsuccessful encoding, with the gamma activity at these sites coupled to the trough of the slow-theta oscillation. These same conditions facilitate LTP in animal models, providing a possible mechanism of action for this effect in human memory. Uniquely in the hippocampus, phase preference during item encoding exhibited a biphasic pattern. Overall, our findings help translate between the patterns identified during basic memory tasks in animals and those present during complex human memory encoding. We discuss the unique properties of human hippocampal PAC and how our findings relate to influential theories of information processing based on theta–gamma interactions.